Molecular profile of Hürthle cell carcinomas: recurrent mutations in the Wnt/β-catenin pathway. Issue 6 (December 2020) - Santana, Nathalie Oliveira; Lerario, Antonio Marcondes; Schmerling, Cláudia Kliemann; Marui, Suemi; Alves, Venancio Avancini Ferreira; Hoff, Ana O; Kopp, Peter; Danilovic, Debora Lucia Seguro
Abstract : Objective: Genomic alterations in Hürthle cell carcinomas (HCC) include chromosomal losses, mitochondrial DNA mutations, and changes in the expression profile of the PI3K-AKT-mTOR and Wnt/β-catenin pathways. This study aimed at characterizing the mutational profile of HCC. Methods: Next-generation sequencing (NGS) of 40 HCC using a 102-gene panel including, among others, the MAPK, PI3K-AKT-mTOR, Wnt/β-catenin, and Notch pathways. HCC was widely invasive in 57.5%, and lymph node and distant metastases were diagnosed in 5% and 7.5% of cases. During follow-up, 10% of patients presented with persistent/recurrent disease, but there were no cancer-related deaths. Results: Genetic alterations were identified in 47.5% of HCC and comprised 190 single-nucleotide variants and 5 insertions/deletions. The Wnt/β-catenin pathway was most frequently affected (30%), followed by MAPK (27.5%) and PI3K-AKT-mTOR (25%). FAT1 and APC were the most frequently mutated genes and present in 17.5%. RAS mutations were present in 12.5% but no BRAF mutation was found. There was no association between the mutational profile and clinicopathological features. Conclusions: This series of HCC presents a wide range of mutations in the Wnt/β-catenin, MAPK and PI3K-AKT-mTOR pathways. The recurrent involvement of Wnt/β-catenin pathway, particularly mutations in APC and FAT1, are of particular interest. The data suggest that mutated FAT1 may represent a potential novel driver in HCC tumorigenesis and that the Wnt/β-catenin pathway plays a critical role in this distinct thyroid malignancy.